Decision support systems VIII : sustainable data-driven and evidence-based decision support : 4th International Conference, ICDSST 2018, Heraklion, Greece, May 22-25, 2018, Proceedings /: sustainable data-driven and evidence-based decision support : 4th International Conference, ICDSST 2018, Heraklion, Greece, May 22-25, 2018, Proceedings. (2018) - Unknown
No abstract available